PENDIDIKAN AGAMA KRISTEN DALAM ERA AI: MENGGUNAKAN KECERDASAN BUATAN UNTUK PERSONALISASI PEMBELAJARAN SPIRITUAL - Waruwu, Yamotani (Jurnal Abdiel: Khazanah Pemikiran Teologi, Pendidikan Agama Kristen dan Musik Gereja, 2024)
The digital era and the emergence of Artificial Intelligence (AI) have presented a significant shift in teaching methods, including in the realm of Christian Religious Education (PAK). This article explores the integration of AI in PAK, with a focus on personalizing spiritual learning. Using a qualitative method with a literature study approach, this study analyzes current sources to understand the potential and challenges of using AI in the context of spiritual education. The results of the study show that AI offers significant opportunities to improve the quality and effectiveness of PAK through personalized learning, deeper analysis of religious texts, and wider access to educational resources. However, the application of AI also presents ethical challenges, including concerns about data privacy, the potential erosion of relational aspects in education, and the risk of widening the digital divide. The study emphasizes the importance of a balanced approach to integrating AI, which involves training educators, developing ethical frameworks, and ongoing theological reflection. In conclusion, while AI has transformative potential in PAKs, its application must be done carefully to ensure that technology supports, not replaces, important aspects of Christian religious education, including authentic character building and spiritual growth.